Nematodes diversity in Mastomys rodents (Rodentia: Muridae) and molecular characterization of Trichuris species in the Mnisi Community, South Africa - Marufu, Munyaradzi Christopher (University of Pretoria, 2024)
Dissertation (MSc (Global One Health))--University of Pretoria, 2023.